PENGARUH DANA PIHAK KETIGA, PERMODALAN, AKTIVA PRODUKTIF DAN LIKUIDITAS TERHADAP JUMLAH PENYALURAN KREDIT PERBANKAN - Rosawati, Yuliani; Pinem, Dahlia (Ekonomi dan Bisnis, 2017)
Banks have an important role in the economic sector especially in the development and economic growth, it is not separated from the role of banks as intermediary institutions. The bank has a duty to collect funds from the public and then channeled back to the community in the form of credit. The lending is not optimal conducted by the bank into the background of this research. This research is a quantitative research that aims to determine the effect of third party funds, capital, earning assets and liquidity assets to total bank credit distribution. The population used in this study is a commercial bank listed on OJK in the period 2011-2015. By using purposive sampling method, it is obtained as many 20 banks as the study samples. The method of analysis used in this study using panel data regression analysis with the program Eviews 8.0 and 5% significance level. The results of this study indicate that the third party funds and liquidity represented by LDR significant positive effect to total banking credit distribution, Capital represented by CAR has not significant effect to total banking credit distribution, while earning assets represented by NPL significant negative effect to total banking credit distribution.